Truth in nonfiction : essays - Lazar, David, 1957- (University of Iowa Press, 2008)
From Elie Wiesel to Benjamin Wilkomirski to David Sedaris, the veracity of writers' claims has been suspect. In this fascinating and timely collection of essays, leading writers meditate on the subject of truth in literary nonfiction. As David Lazar writes in his introduction, "How do we verify? Do we care to? (Do we dare to eat the apple of knowledge and say it's true? Or is it a peach?) Do we choose to? Is it a subcategory of faith? How do you respond when someone says, 'This is really true'? Why do they choose to say it then?"